Approach to the functional state control of the complex technical systems during the operating interval of their life cycle - Чепіженко, В.І. (Proceedings of National Aviation University (archive), 2010)
Conceptsnotion «The functional state» difficult technical system and «the system functional state control in large and whole» are entered. The including chartof control the system by the functional state is offered for providing of functioning of the difficult technical system on all of operating interval of its life cycle.